A new oryzomyine (Rodentia: Sigmodontinae) from the Quaternary of Curaçao (West Indies) - Zijlstra, Jelle S. (Zootaxa, 2012)
A collection of 17 isolated rodent molars from a cave in the eastern part of Duivelsklip, Curaçao, Dutch West Indies, isdescribed as Dushimys larsi, new genus and species. The new species is characterized by relatively large size, broad mo-lars, absence of mesolophid and presence of anterolophid and anterolabial cingulum on m3, absence of metaloph on M3,and m2 with three roots. Phylogenetic analysis could not conclusively resolve the position of the new species, and it isprovisionally regarded as a representative of an otherwise unknown oryzomyine genus. The material is likely middle Pleistocene in age.